PERAN KURIKULUM LOGIKA TERHADAP HASIL BELAJAR IPS SISWA DI SEKOLAH ALAM SOU BOGOR - Fatmawati Fatmawati; Yusrizal Yusrizal; Baihaqi Siddik Lubis; Fathyah Sauma Rafiqah (JURNAL TEMATIK, 2020)
Education is one of the important things in providing knowledge to students, knowledge can be obtained anywhere and anytime, especially at school. School is a tool means of receiving and providing teaching provided by educators to students. The purpose of this study was to determine how important the role of the logic curriculum is to the social studies learning outcomes of students at SOU Bogor Natural Schools. The approach used in this research is a qualitative approach with a descriptive type. The data collection techniques used were observation, interview and documentation. The results showed that. 1) The Logic Curriculum is carried out every time of learning, each learning is associated with the logic curriculum; 2) The logic curriculum makes students understand more about what is being taught and provides new knowledge for each student; 3) the logic curriculum as a determinant of improving student learning outcomes at the SoU Parung Bogor natural school, if the curriculum is implemented properly, the learning outcomes of children are also well formed